2020
DOI: 10.1038/s41422-020-0314-9
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of senescent cells by β-galactosidase-targeted prodrug attenuates inflammation and restores physical function in aged mice

Abstract: Cellular senescence, a persistent state of cell cycle arrest, accumulates in aged organisms, contributes to tissue dysfunction, and drives age-related phenotypes. The clearance of senescent cells is expected to decrease chronic, low-grade inflammation and improve tissue repair capacity, thus attenuating the decline of physical function in aged organisms. However, selective and effective clearance of senescent cells of different cell types has proven challenging. Herein, we developed a prodrug strategy to desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
167
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 245 publications
(197 citation statements)
references
References 72 publications
2
167
0
1
Order By: Relevance
“…This safety profile was further supported by comparison to SSK1 effector gemcitabine, an approved clinical drug. 9 Therefore, the in-vivo safety of SSK1 demonstrated in this and our recent studies provides a foundation for the potential of clinical applications in treating COVID-19 patients.…”
Section: Dear Editormentioning
confidence: 69%
See 2 more Smart Citations
“…This safety profile was further supported by comparison to SSK1 effector gemcitabine, an approved clinical drug. 9 Therefore, the in-vivo safety of SSK1 demonstrated in this and our recent studies provides a foundation for the potential of clinical applications in treating COVID-19 patients.…”
Section: Dear Editormentioning
confidence: 69%
“…8 We found that SSK1 treatment efficiently decreased macrophage numbers and their infiltration in lung injured mouse model, which accompanied with significant attenuation of inflammation. 9 Basing on these results, we reasoned that SSK1 is a promising new drug that can be applied to target macrophages and treat excessive inflammation in COVID-19 patients. In this study, we investigated the therapeutic effects of SSK1 in SARS-CoV-2-infected nonhuman primate model.…”
Section: Dear Editormentioning
confidence: 99%
See 1 more Smart Citation
“…Senolytics have emerged as an exciting area with great therapeutic promise in aging (Xu et al 2018;Zhu et al 2015), cancer (Dörr et al 2013;Guerrero et al 2019), and other diseases. In mice, clearance of senescent cells restores tissue homeostasis and delays age-related dysfunction (Baar et al 2017;Baker et al 2011;Cai et al 2020;Baker et al 2016). Furthermore, clinical trials of the senolytic combination dasatinib and quercetin have shown encouraging results (Hickson et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…3 β-D-galactosidase [EC 3.2.1.23] (β-Gal) is a glycoside hydrolase enzyme that catalyzes the hydrolysis of glycosidic bonds, producing monosaccharides from β-galactosides 1 . β-Gal has been extensively studied because of its nutritional, biotechnological and therapeutic impact 2,3 . In our laboratory, we are interested in describing how the recombinant production of proteins, particularly β-Gal, and the purification strategies could modulate their structure/function relationship.…”
mentioning
confidence: 99%